Perpetration, Victimhood, and Blame: Australian Newspaper Representations of Domestic Violence, 2000–2020 - Karageorgos, Effie (Violence against women, 2024)
Newspaper media plays a significant role in forming a public understanding of domestic violence. This article analyses 554 articles from 24 newspapers across Australian states and territories published between 2000 and 2020 that describe specific instances of domestic violence. It examines whether such violence is framed as a systemic issue or as a collection of individual events, as well as how such representations of perpetrators and victims displace both “blame” and “victimhood.” Although positive aspects of reporting can be observed, the tendency within newspaper articles to blur distinctions between perpetrators and victims distorts the true scale of domestic violence in Australia.